Personal Choice: A Blessing or a Burden, or Both? A Cross-cultural Investigation on Need for Closure Effects in two Western and two East-Asian societies - ROETS, Arne (Institutional Knowledge at Singapore Management University, 2014)
The present study investigates the role of dispositional need for closure (NFC) in how individuals within a particular culture perceive and appreciate choice. Data sets from the US (283 adults), Europe (263 adults and 427 students), China (218 adults and 309 students) and Singapore (258 students) were collected. The results showed that in Western cultures, people perceived choice in a linear way as either a burden or a blessing, whereas in Chinese culture, such opposition between perspectives did not appear, and individuals generally saw choice as both burden and blessing simultaneously. In Western cultures, high dispositional NFC was strongly associated with viewing choice-as-a-burden, whereas Chinese respondents with a high NFC perceived choice as a blessing and a burden simultaneously. The Singaporean results were similar to the Western pattern. These findings are discussed in terms of the NFC literature and cultural differences in dialectic versus differentiation thinking styles.